2021
DOI: 10.3389/fnut.2021.641939
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Phenolic Metabolites and Biological Activities of Pumpkin Leaves (Cucurbita moschata Duchesne ex Poir.) During Blanching

Abstract: Pumpkin leaves (Cucurbita moschata Duchesne ex Poir.) are popularly consumed in Sub-Saharan Africa and Asia. Blanching the leaves before drying is a method of preservation during off-season. In this study, different blanching treatments and media are used to test the changes in non-targeted phenolic compounds, antioxidant capacity (FRAP and ABTS activity), in vitro α-glucosidase activity and cell cytotoxicity of pumpkin leaves. Steam blanching in plain water led to the highest retention of total phenolic conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 46 publications
0
25
0
Order By: Relevance
“…In its MSE spectrum, peak 7 had a base peak ion at m / z 300 [M-H-147-162] as a result of the successive loss of rhamnose and the galactose moiety. The fragment ion at m / z 300 indicated that the compound is a quercetin derivative [ 26 ]. Peak 7 was tentatively identified as quercetin-3-galactoside 7-rhamnoside.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In its MSE spectrum, peak 7 had a base peak ion at m / z 300 [M-H-147-162] as a result of the successive loss of rhamnose and the galactose moiety. The fragment ion at m / z 300 indicated that the compound is a quercetin derivative [ 26 ]. Peak 7 was tentatively identified as quercetin-3-galactoside 7-rhamnoside.…”
Section: Resultsmentioning
confidence: 99%
“…A secondary peak was observed at m / z 463 [M-H-146] as a result of the loss of the rhamnose moiety from the parent ion. Another secondary fragment observed at m / z 179 was due to retrocyclisation following fission of the C ring of quercetin [ 26 ]. As such, peak 7 was tentatively identified as quercetin-3-glucoside 7-rhamnoside (rutin).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Predominant polyphenolic metabolites present in leaves of var. Butternut squash ( C. moschata) were extracted and quantified using a Waters Synapt G2 Quadrupole time-of-flight (QTOF) mass spectrometer (MS), hyphenated to a Waters Aquity ultra-performance liquid chromatograph (UPLC) (Waters, Milford, MA, USA), as described earlier by Mashitoa et al ( 3 ). Briefly, the instrument was used in the negative mode electrospray ionization with a cone voltage of 15 V, a desolvation temperature of 275°C, and desolvation gas of 650 L/h, and the rest of the MS settings were optimized for best resolution and sensitivity.…”
Section: Methodsmentioning
confidence: 99%
“…The FAO/WHO ( 2 ) recommends a serving size of 80–100-g green leafy vegetables in four to five servings for adults. The nutritional information present in the leaves of pumpkin species C. moschata is given in detail in the study of Mashitoa et al ( 3 ). The leaves of pumpkin species ( C. moschata ) are functional vegetables due to their higher phenolics, flavonoid content, and antioxidant scavenging activity ( 4 – 6 ).…”
Section: Introductionmentioning
confidence: 99%